The Role of Distributed Leadership in Achieving Organizational Ambidexterity among Female Leaders of Public Schools in AL- Madinah Al-Munawwarah from the Point of Views of Female Teachers - Al-Rehili, Asma'a Saleem (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the role of distributed leadership in achieving organizational ambidexterity among Female Leaders of Public Schools in AL- Madinah Al-Munawwarah from the Perspective of Female Teachers, identify the reality of their practice of both distributed leadership and organizational ambidexterity, to reveal the relationship between distributed leadership and organizational ambidexterity ,and to reveal the differences between the Perspective of Female Teachers about the role of distributed leadership in achieving organization ambidexterity among them according to their number of years of service variable and educational qualification variable. To achieve the purpose of the study, the study used the descriptive survey method and a questionnaire as the study tool for data collection. The study sample consists of 373 teachers from Public Education Schools in AL- Madinah Al-Munawwarah. The data was analyzed by using the Statistical Package for the Social Sciences program (SPSS). The study revealed the following results: the practice of both distributed leadership and the organizational ambidexterity among leaders came to a large extent, It also showed the existence of a positive statistically significant relationship between the estimation of education school teachers for the leaders ’practice of distributed leadership and their degree of organizational ambidexterity, and there are no differences with statistical evidence between the averages of the study sample about the role of distributed leadership in achieving organizational ambidexterity among the leaders of Public Education Schools in AL- Madinah Al-Munawwarah from the teachers’ Perspective according to their number of years of service variable and educational qualification variable. Finally, the study recommends putting an Excellence award for an Effective leadership practice and establish a local digital platform for consultancies.
Keywords: leadership; distributed leadership; organizational ambidexterity